2021
DOI: 10.1108/xjm-02-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Family-friendly policies, supervisor support and job satisfaction: mediating effect of work-family conflict

Abstract: Purpose The purpose of this paper is to investigate the effect of perceived support from family-friendly policies and supervisors on job satisfaction of employees by incorporating work-family conflict as a mediator. Design/methodology/approach Primary data were collected from 369 employees working in different organizations from the service sector in India. Smart PLS software was used to perform partial least square structural equational modeling. Findings The result confirms that both family-friendly poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
(119 reference statements)
5
16
0
3
Order By: Relevance
“…As indicated in Table 4, original sample value (-0.306), T-statistics value (1.969 > 1.96) and p-value (0.05 = 0.05), hence supported H1. This result is consistent with previous research by Yadav & Sharma (2021); Survival & Dewi (2013);and Martinez-Sanchez et al, (2018) with conclusion that family-friendly policies are important to help employee reduce their family issue dealing with work issue.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As indicated in Table 4, original sample value (-0.306), T-statistics value (1.969 > 1.96) and p-value (0.05 = 0.05), hence supported H1. This result is consistent with previous research by Yadav & Sharma (2021); Survival & Dewi (2013);and Martinez-Sanchez et al, (2018) with conclusion that family-friendly policies are important to help employee reduce their family issue dealing with work issue.…”
Section: Resultssupporting
confidence: 93%
“…therefore, H2 is not supported. The findings also consistent with previous study by Yadav & Sharma (2021); Bae & Yang (2017) with stated that family-friendly policies have disadvantage, with findings that busy schedule can produce a negative effect on work satisfaction in terms of the type of work environment at home.…”
Section: Resultssupporting
confidence: 92%
“…Some researchers found that the time-sharing ratio between work and family is a critical determinant of attaining balance (Lonska et al. , 2021; Thilagavathy and Geetha, 2021; Yadav and Sharma, 2021). Once an employee can find a balance between work and life, there will be spillover effects on the organization regarding superior performance (Huang et al.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Other studies have shown that FFP also reduces work-family conflict [12][13][14][15][16][17]. [17] stated that FFP could reduce work-family conflict because of promotes working parents to be mindful both in the workplace and at home.…”
Section: Introductionmentioning
confidence: 99%